2014
DOI: 10.1111/cas.12558
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen adversely affects the prognosis of patients with lung adenocarcinoma

Abstract: Estrogen has been postulated to contribute to the development and progression of lung cancer. We examined the epidemiologic evidence, explored the characteristics of estrogen receptors (ER) in lung adenocarcinoma, and investigated the effect of estrogen on lung cancer cell migration, including the signaling pathway involved. For epidemiologic evidence, a total of 1434 consecutive non-small cell lung cancer patients who underwent standardized staging and homogenous treatment were prospectively enrolled from Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 45 publications
3
36
0
3
Order By: Relevance
“…It is known that oestrogen (E2) elicits a stronger immune reaction than testosterone, and the immunoregulatory effect of E2 contributes to the susceptibility of women to AIDs . In addition, accumulating evidence has shown that OPN production is E2‐dependent, which further supports the concept that E2 can modulate OPN bioactivity . Despite there being no significant difference in OPN levels between women and men in GD, we believe that E2 might still modify OPN's function at a certain level, and subsequently facilitate OPN production, and contribute to GD development and promote a stronger association of OPN levels with TSHRAb levels and thyroid function in women than in men.…”
Section: Discussionsupporting
confidence: 55%
“…It is known that oestrogen (E2) elicits a stronger immune reaction than testosterone, and the immunoregulatory effect of E2 contributes to the susceptibility of women to AIDs . In addition, accumulating evidence has shown that OPN production is E2‐dependent, which further supports the concept that E2 can modulate OPN bioactivity . Despite there being no significant difference in OPN levels between women and men in GD, we believe that E2 might still modify OPN's function at a certain level, and subsequently facilitate OPN production, and contribute to GD development and promote a stronger association of OPN levels with TSHRAb levels and thyroid function in women than in men.…”
Section: Discussionsupporting
confidence: 55%
“…Therefore, FRBI interfered with FSH-FSHR interaction leading to a blockage of FSH action [3]. Currently, little information has been recorded about FRBI effects on follicular development and reproduction functions in human and animals [2, 13]. In the present study, different doses of FRBI were added into the IVM medium for sheep COCs so as to assess FRBI effects on IVM and apoptosis of sheep COCs.…”
Section: Discussionmentioning
confidence: 99%
“…These signaling cascades adjusted by FSH and LH in the granulosa cells play a crucial role in follicular development and ovulation [11]. However, the exact mechanism of FRBI actions remains still unclear and the regulatory signaling pathways are undetermined [2, 12, 13]. IP3 is an important intracellular second messenger that participates in signal transduction pathways in diverse cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen is thought to play an important role in carcinogenesis in some carcinomas. One laboratory study demonstrated that estrogen upregulates osteopontin expression and promotes cancer cell migration via estrogen receptor beta (ERβ) activation in the MEK/ERK signaling pathway (17). Furthermore, Hsu et al (18) evaluated gender-associated differences on survival in non-smoker patients with lung adenocarcinoma and noted that elderly women had a more favorable survival outcome than elderly males.…”
Section: Discussionmentioning
confidence: 99%